"Your Gender is Valid": Microaffirmations in the Romantic Relationships of Transgender Individuals. Issue Volume 13:Issues 1(2019) (2nd January 2019) - Pulice-Farrow, Lex; Bravo, Alex; Galupo, M. Paz
Abstract: Microaffirmations are small, interpersonal interactions that communicate validation for an identity. The present study focuses on transgender microaffirmations received from romantic partners. Participants included 339 self-identified transgender adults in a romantic relationship (currently or within the past 5 years). Participants were recruited via social media and snowball sampling and took an online survey detailing their experiences in romantic relationships. Participant responses were analyzed via thematic analysis, resulting in seven relationship-salient themes: (1) acknowledging and using cisgender privilege, (2) centering on partner's identity, (3) affirming gender(less) presentation, (4) helping partner process identity, (5) seeking permission, (6) using affirming language, and (7) acknowledging milestones. Findings emphasize the importance of positive aspects of romantic relationships. Implications for working with transgender clients are discussed.